Spillover effects of government initiatives fostering entrepreneurship on the access to bank credit for entrepreneurial firms in Europe - Moro, Andrea; Maresch, Daniela; Fink, Matthias; Ferrando, Annalisa; Piga, Claudio (Journal of Corporate Finance, 2020)
We explore the role of government initiatives fostering entrepreneurship—in the form of tax advantages and government support—in influencing the probability that entrepreneurial firms obtain bank credit and are not discouraged from applying for a loan. We propose that government initiatives fostering entrepreneurship should allow entrepreneurial firms to access more bank credit by reducing the risk incurred by lenders. We simultaneously estimate the probability of obtaining credit when a firm applies for a loan and the probability that the firm has been discouraged when it does not apply for a loan. In both cases we control for endogeneity. Our results are based on 18,872 observations (from the European Central Bank (ECB) SAFE dataset and Global Entrepreneurship Monitor – GEM) and show that government initiatives improve the probability of entrepreneurial firms obtaining bank credit but do not affect the probability of being discouraged from borrowing. The results also suggest that government initiatives fostering entrepreneurship are of most benefit to younger, smaller, high-growth, and more innovative firms that operate in contexts where the demand for, and accordingly the competition for, bank credit is strongest.